Evaluating the hedging effectiveness in crude palm oil futures market during financial crises - Go, Y.H.; Lau, W.Y. (2014)
This study examines whether there is a significant change in hedging effectiveness on Crude Palm Oil (CPO) futures market from January 1986 to December 2013. Eight hedging models with different mean and variance-covariance specifications have been evaluated. As the volatility of spot and futures markets is not similar across time, both markets exhibit asymmetric information transmission. Our results of out-of-sample evaluation show, firstly, the time-varying hedge ratios with basis term produce better performance during both financial crises. Secondly, high dynamic hedge ratios during the Asian financial crisis contribute to the support for CCC-GARCH model. Thirdly, during global financial crisis, BEKK-GARCH model appears to provide more risk reduction as compared to others. From the perspective of economic modeling, incorporating the basis term in modeling the joint dynamics of spot and futures returns during the crises provide better results. This study recommends that CPO market participants to adjust their hedging strategies in response to different movement in market volatility.